KECEMASAN DAN PSIKOTERAPI ISLAM (Model Psikoterapi Al-Qur’an dalam Menaggulangi Kecemasan Santri Lembaga Tinggi Pesantren Luhur dan Pondok Pesantren Baiturrahmah di Kota Malang) - Drs. Mulyadi, M. Ag, Rifa Hidayah, M.Si, M. Mahfur, M.Si (El-QUDWAH, 2006)
Anxiety is unpleasant feeling happened when someone is depressed or has spiritual conflict. In Al-Quran we can find a lot of verse related to human psychology that theoretically can be used as psychotherapy references to overcome anxiety. Al-Quran offers solution to have serenity through its verses that tell us how to face the problems in life without anxiety.Using qualitative research method and grounded theory approach, this research is aimed to know the Islamic psychotherapy model using verses in Al-Quran to overcome anxiety in Islamic boarding school Luhur and Baiturrahmah Malang. The research is focused on the process of present phenomenon, the conceptual framework is taken from the data, rather than from the former research, although it still gives influences to the result of the research. The research method is done through thorough interview, observation, documentation, and anxiety test. And the data analysis uses inductive approach.The result of the research shows that most Islamic psychotherapy methods using Al-Quran as media to overcome anxiety done by therapist (“kiai” and those who are given the authority to give therapy) in Islamic boarding school Luhur and Baiturrahmah are using self and direct therapy. Both use integrative approach by method of intuition that is done through activities such as praying, fasting, and reading verses in Al-Quran in solitude. The anxiety test shows that after the therapy 95% of students in those Islamic boarding schools have decreased their anxiety level. It indicates that Islamic therapy is very effective.Kata kunci: Kecemasan, psikoterapi, pondok pesantren